Website Based Floor Plan Design for Henricus Constant and Mikael Unika Soegijapranata Buildings - Putra, Sie Irfan Eka; Prasetya, FX. Hendra; Nugroho, Agus Cahyo (Soegijapranata Catholic University, 2024)
This study explains how influential technological progress is in several aspects, in this study it refers to aspects of education, knowledge, and facilities for students regarding floor plans. And with existing technological advancements, it doesn't make it difficult for students to find information boards or bulletin boards.There are several methods of analysis, namely, Primary Data Sources and Secondary Data Sources. The second uses the Data Collection method in this method which is also divided into several sections, namely: Collection of Questionnaires or Questionnaires, Literature Study and Interviews. The third uses the Testing method which is divided into several tests, namely: Application Testing, Testing Model Development, Methodology Flowchart, Framework of Mind.